THE EFFECT OF PROFITABILITY, LEVERAGE, COMPANY SIZE AND INDUSTRY TYPE ON SUSTAINABILITY REPORT ASSURANCE - Hafindatama Akbar Privika; Bunga Maharani; Ririn Irmadariyani (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2021)
ABSTRACTThis study aims to analyze the effect of profitability, leverage, company size and type of industry on the assurance of sustainability reports in companies listed on the Indonesia Stock Exchange for the period 2017-2019. This research is a quantitative research. The sample selection was carried out using purposive sampling method. The data used is secondary data obtained from the company website and from the IDX website. The data population in this study are all companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample is 27 companies. The results showed that profitability, leverage and type of industry had no effect while firm size had an effect on the assurance of sustainability reports.Keywords: assurance, leverage, size, sustainabilityABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh profitabilitas, leverage, ukuran perusahaan dan jenis industri terhadap assurance laporan berkelanjutan pada perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2019. Penelitian ini merupakan penelitian kuantitatif. Pemilihan sampel dilakukan dengan metode purposive sampling. Data yang digunakan adalah data sekunder yang diperoleh dari website perusahaan dan dari website BEI. Populasi data dalam penelitian ini adalah seluruh perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2017-2019. Sampel penelitian adalah 27 perusahaan. Hasil penelitian menunjukkan bahwa profitabilitas, leverage dan jenis industri tidak berpengaruh sedangkan ukuran perusahaan berpengaruh terhadap assurance laporan keberlanjutan.Kata kunci: assurance, keberlanjutan, leverage, ukuran